Longitudinal Study of Plasma Visfatin/Nicotinamide Phosphoribosyltransferase (NAMPT) Levels in Healthy Pregnant Women - Nunes, Priscila R. [UNESP]; Cavalli, Ricardo C.; Belo, Vanessa A.; Sandrim, Valeria C. [UNESP]; Luizon, Marcelo R. [UNESP] (My University, 2023)
Visfatin/nicotinamide phosphorybosil transferase (NAMPT) is a novel adipocytokine with potential roles in the pathophysiology of metabolic disorders, including gestational disorders. However, there is no clear interpretation regarding the circulating visfatin levels in a healthy pregnancy. Therefore, we conducted the first longitudinal study of plasma visfatin levels that followed up healthy pregnant women until the third trimester, including the postpartum period (PPP). The study recruited healthy women with singleton pregnancy who were not using any drug (including tobacco and alcohol). We have excluded pregnant women who did not attend all scheduled exams and developed gestational diabetes or hypertension, obesity, preeclampsia, or any infections during pregnancy. Nine women were considered eligible and examined during all three trimesters of pregnancy and between 8 and 12 weeks postpartum (PPP). Visfatin/NAMPT concentrations were measured in EDTA-plasma by ELISA. The mean age of pregnant women included was 22±5 years (54% primiparous), and the mean of gestational age at delivery was 40±1.2 weeks. Mean systolic and diastolic blood pressures were 90 and 70 mmHg, respectively. Mean values (± standard error mean) of visfatin concentrations (μg/L) during trimesters were 11.38±1.45 (first, 11–14 weeks), 9.18±1.82 (second, 20–24 weeks), 18.67±2.65 (third, 34–36 weeks), and 10.12±1.49 in the PPP. The value of the third trimester was significantly higher than the second trimester, and significantly reduced in the PPP (p<0.05, ANOVA with Bonferroni’s multiple comparison tests). Visfatin/NAMPT levels are significantly lower in the PPP, suggesting that factors stimulating its production would be limited to pregnancy, thereby contributing to its potential application as a biomarker in pregnancy complications.
Keywords: Adipocytokines; Cytokines; extracellular NAMPT (eNAMPT); Nicotinamide phosphoribosyltransferase (NAMPT); Pregnancy; Visfatin